2013
DOI: 10.1101/cshperspect.a014332
|View full text |Cite
|
Sign up to set email alerts
|

Control of Vertebrate Development by MYC

Abstract: The study of MYC has led to pivotal discoveries in cancer biology, induced pluripotency, and transcriptional regulation. In this review, continuing advances in our understanding of the function of MYC as a transcription factor and how its transcriptional activity controls normal vertebrate development and contributes to developmental disorders is discussed. During embryonic development, a great diversity of cell types are rapidly produced concomitant with their organization into the different functional tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 151 publications
0
28
0
1
Order By: Relevance
“…Conditional deletion of Mycn in early neural stem and progenitor cells of this mouse led to profound cerebellum defects, in part owing to the failure to suppress two cyclin-dependent kinase inhibitory proteins (CKIs), p18 Ink4c and p27 Kip1 (Knoepfler et al 2002). Remarkably, these cerebellar defects could be partially rescued by the loss of the two CKIs suggesting that MYCN inhibition of p18 Ink4c and p27 Kip1 expression is required for proper cerebellar development (Knoepfler et al 2002;Zindy et al 2006;Hurlin 2013).…”
Section: Myc In the Developing Posterior Fossamentioning
confidence: 99%
“…Conditional deletion of Mycn in early neural stem and progenitor cells of this mouse led to profound cerebellum defects, in part owing to the failure to suppress two cyclin-dependent kinase inhibitory proteins (CKIs), p18 Ink4c and p27 Kip1 (Knoepfler et al 2002). Remarkably, these cerebellar defects could be partially rescued by the loss of the two CKIs suggesting that MYCN inhibition of p18 Ink4c and p27 Kip1 expression is required for proper cerebellar development (Knoepfler et al 2002;Zindy et al 2006;Hurlin 2013).…”
Section: Myc In the Developing Posterior Fossamentioning
confidence: 99%
“…Brachyury controls a key developmental process called gastrulation: this produces the body's three major cell layers, and the protein subsequently mediates differentiation of one of these layers, the mesoderm. In animals, both Myc and Brachyury function by binding to enhancers to regulate the transcription of a network of downstream genes 7,8 . Remark ably, SebéPedrós et al found that these downstream gene networks are conserved in animals and Capsaspora.…”
mentioning
confidence: 99%
“…Indeed, genetic ablation of MYC in mice is embryonic lethal at an early stage of gestation (between days 9.5 and 10.5), with failed hematopoietic development (Davis et al 1993;Hurlin 2013). Although subsequent studies have shown tolerance of tissue-specific MYC loss or downregulation, such as in the liver and small intestine (Bettess et al 2005;Hurlin 2013), concerns remain that pharmacologic inhibition of MYC may feature a narrow therapeutic index.…”
mentioning
confidence: 99%
“…Although subsequent studies have shown tolerance of tissue-specific MYC loss or downregulation, such as in the liver and small intestine (Bettess et al 2005;Hurlin 2013), concerns remain that pharmacologic inhibition of MYC may feature a narrow therapeutic index. For example, tolerance of MYC loss in intestinal epithelium could be conferred by compensatory up-regulation of MYCN (Bettess et al 2005;Hurlin 2013), suggesting that selective inhibition of MYC-family isoforms may be required to firmly establish a therapeutic index.…”
mentioning
confidence: 99%